BUILD NETWORKS FROM SIMPLE POINT (POINT TO POINT / PEER TO PEER) - Andi Dwi Prasetyo; Ir.Aqwam Rosadi Kardian, MM (Jurnal Sistem Informasi, 2003)
The development of computer technology especially very rapidly in recent years. Formerly a large computer, now you are getting physically smaller, but has a very high performance and very compact. Year after year people began to use computers very well known with a personal computer (PC). Origins of personal computers (PCs) are used by each person and stand alone (stand alone). The computers are not connected or another. For stand alone PC, the application program must be loaded onto each PC, and prosesntya must move your PC.Based on this, the author has the idea to combine some of the PC into a simple network of networks known as point to point (point to point), the idea is essentially the use of resources together.